REASSIGNING THE TRANSSEXUAL SUBJECT: EITHER/OR, BOTH/AND? - McLuckie, Kerry (PINS-Psychology in Society, 2026)
The phenomenon of transsexualism offers a number of interesting challenges to conceptions of gender and body politics. The physical reconstruction of the body to align it with personal perceptions of gender suggests that gender is not a physiological given, but rather an aspect of identity/subjectivity. In following this line of argument transsexualism can be conceptualised as a post-modem identity project, where the body is actively fashioned to meet people’s construction of subjectivity. This notion, however becomes problematic when one considers that transsexualism still adheres very strongly to binary notions of gender as categorised by the division of male/female; and sex reassignment can thus be seen as a modernist project enforcing notions of coherence between the signifier (the body) and the signified (gender). This article explores the history of transsexualism, the discusses some of these contradictions in "transsexualism’; with reference to concepts of the body, identity and identity projects in the context of the sex reassignment process.